Biosorption of Cr(III) using in natura and chemically treated tropical peats - Batista, A. P. S.; Romao, L. P. C.; Arguelho, M. L. P. M.; Garcia, C. A. B.; Alves, J. P. H.; Passos, E. A.; Rosa, André Henrique [UNESP] (Elsevier B.V., 2009)
The physicochemical characteristics of three Brazilian pears were investigated using elemental analysis, scanning electron microscopy (SEM), X-ray diffractometry (XRD) and studies of Cr(III) biosorption based on adsorption isotherms. Adsorption of Cr(III) by in natura peat from Santo Amaro das Brotas (Sergipe State) was much greater than by peats from either Ribeirao Preto (São Paulo State) or Itabaiana (Sergipe State), with adsorption capacities (q) of 4.90 +/- 0.01, 1.70 +/- 0.01 and 1.40 +/- 0.01 mgg (1), respectively. Pre-treatments with HCl and NaOH + HCl reduced adsorption by the Santo Amaro clas Brotas peat, showing that adsorption efficiency was associated with the amount of organic matter present. Conversely, increase in the mineral content following pre-treatment increased adsorption of Cr(III) by the Ribeirao Preto and Itabaiana peats. Highest adsorption (retention >95.0%) was achieved at equilibrium pH 4.0 using the Santo Amaro das Brotas peat. Experimental data for the adsorption of Cr(III) from aqueous solution onto this peat were fitted to the Langmuir equation, from which an equilibrium adsorption capacity, q(max), of 5.60 mgg(-1) was obtained, which was close to the experimentally determined value. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chromium; Peat; Chemical pre-treatment